THE IMPORTANCE OF PREHOSPITAL RECOGNITION OF ST SEGMENT ELEVATION IN THE AVR LEAD IN ACUTE CORONARY SYNDROME - Todorović, Gordana; Joldzic, Aleksandar; Vesic, Dragana (Halo 194 Scientific Journal of Emergency Medicine, 2020)
Objective The objective of the article is to present how educated the EMS doctors included in the STEMI network are in recognizing and treating the aVR lead elevation, as an atypical ECG finding.Case report Three patients with chest pain from 30 minutes to 2.5 hours are presented. The ECG recording  sST depressions >1mm in 6 or more leads (I, II, III, aVL, aVF, V2-V6) coupled with a 3-4mm ST elevation in the aVR lead and similar less pronounced ST elevation in V1. The strategy for primary PCI had been initialized,  after consultation with interventional cardiologists and having taken the initial dose of dual antiplatelet therapy, transported to the hospital catheterization labs.Conclusion ST segment depression of 1 mm or more in six or more leads (inferolateral depression) coupled with ST segment elevation in aVR and/or V1 points to the three-vessel disease (3VD) or left main coronary artery (LMCA) obstruction.
Keywords: aVR elevation, atypical ECG, EMS